Produtividade da canola sobressemeada à soja - Leonardi, Mateus (2019)
Oversowing is a technique which consists in the spreading of seeds of the subsequent crop before the end of the crop cycle that is in the developing field, especially for annual summer crops, allowing the germination and establishment of the crop to be explored prior to harvesting, crop harvest at the end of the cycle, resulting in a significant gain in time. The use of this technique allows intensification of the cropping systems, allowing more harvests in less time for the next harvest. The objective of this study was to verify if it is possible to establish canola in soybean oversowing when it is found in the R5 and R7 phenological stages in the central region of the Rio Grande do Sul State. The study was carried out in the agricultural year of 2018, in the experimental field of the Federal University Santa Maria, Santa Maria, RS. A randomized complete block design was used, in a 2 x 4 factorial scheme, with 4 replications, being the density factor in the main plot 3 kg ha-1 (recommended for row sowing), 6 kg ha-1., 12 kg ha-1 and 18 kg ha-1 and the soybean crop development stage factor (R5 and R7), and a control sown under no-tillage was also implemented following the recommendation for the crop immediately after the soybean harvest. During the canola plant development cycle, the initial plant stand was determined, and from the density of 6 kg ha-1 the recommended plant density for the crop was reached. When the canola plants reached maturity, the treatments were harvested, yield components were measured and yield was determined. The best treatment for Santa Maria was the 6 kg ha-1 overgrowth performed at soybean R7 stage.